Issues on the safety of workers at high rise building construction in Malaysia / Che Mohammad Shafiq Aiman Che Othman - Che Othman, Che Mohamad Shafiq Aiman (2021)
Safety issues in high rise building construction is very dangerous issues and need to take seriously because it can cause the big damage to the building, project and also to the company who managed it. The objective of this study is to the analysis of the type of accident occurrence and causes of accident in the Malaysia high rise construction site. Lastly, to identify the solution on overcome the safety issue in high rise construction site. This involved Qualitative approaches whereby questionnaire had been distribute to the worker who work at high rise construction site in Malaysia. Forty one respondents were received and the data were analysed on mean and percentage value of the type and occur of accident in high rise construction. Next, based on the finding, it can be conclude that there are many types and occur accident in the safety issues on the high rise construction. It also has several solution and recommendation to overcome the problem in this issues